Perencanaan Angkutan Feeder dari Terminal Rajekwesi ke Stasiun Bojonegoro Berdasarkan Analisis Supply - Demand - Zabda Dimas Anugrah Illahi; Nugroho Utomo; Fithri Estikhamah (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Rajekwesi Bojonegoro Terminal is a class A terminal that provides facilities and services for public transportation and passengers. This terminal functions as a destination point for village or intercity transportation that supports the needs of travelers. From the existing conditions, there are many workers from villages who go to Surabaya. They usually leave their homes to the terminal using private vehicles, motorcycle taxis, or pedicabs. Currently, there is no public transportation connecting the village with Nganjuk Terminal. Therefore, the author made a plan for passenger transportation to Nganjuk Terminal in order to meet these transportation needs. This research was conducted at Bojonegoro Station and Rajekwesi Bojonegoro Terminal through a field survey. A total of 200 respondents were taken through questionnaires and interviews to collect primary and secondary data at both locations. After the data was collected, the next step was processing and analysis by summarizing the results of the questionnaire and calculating the transportation needs and microbus fares per passenger. From the questionnaire, information was obtained about the social and economic characteristics of the respondents and their travel profiles. What is obtained from the processing and analysis of integrated transportation planning shows a load factor value of 0.7, a planned travel speed of 33 km/hour, a circulation time of 5.6 minutes, a headway of 5.1 minutes, a frequency of 8 vehicles, a maximum waiting time of 5.1 minutes, and the need for 1 vehicle with a distance of 2 km from the Station to the Rajekwesi Terminal. The fare for microbus passengers with a capacity of 16 seats in zone 1 is IDR 2,700 per passenger.